Energetic particle-induced geodesic acoustic modes on DIII-D. (1st November 2022) - Lin, D.J.; Heidbrink, W.W.; Crocker, N.A.; Du, X.D.; Nazikian, R.; Van Zeeland, M.A.; Barada, K.
Abstract: Various properties of the energetic particle-induced geodesic acoustic mode (EGAM) are explored in this large database analysis of DIII-D experimental data. EGAMs are n = 0 modes with m = 0 electrostatic potential fluctuations (where n / m = toroidal/poloidal mode number), m = 1 density fluctuations, and m = 2 magnetic fluctuations. The fundamental frequency (∼20–40 kHz) of the mode is typically below that of the traditional geodesic acoustic mode frequency. EGAMs are most easily destabilized by beams in the counter plasma current (counter- I p ) direction as compared to co- I p and off-axis beams. During counter beam injection, the mode frequency is found to have the strongest linear dependence (correlation coefficient r = −0.71) with the safety factor ( q ). The stability of the mode in the space of q and poloidal beta ( β p ) shows a clear boundary for the mode stability. The stability of the mode depends more strongly on damping rate than on fast-ion drive for a given injection geometry.